PITHECANTHROPUS ERECTUS BATIK FOR HAUTE COUTURE CLOTHES: A BLEND OF PRIMITIVE AND MODERN STYLES - Hermawati, Dwi Puji (Institut Seni Indonesia Surakarta, 2023)
ABSTRACTThe source of the idea for the creation of this final project is the discovery of the Pithecanthropus Erectus fossil which is enshrined in the Song Terus Pacitan museum, this discovery is one of the earliest evidences of human evolution in prehistoric times. Phitechanthropus Erectus is an ancient human species that lived 1.9 million years ago. The characteristics of ancient humans, Phitechanthropus Erectus, had a more robust body than their predecessors. The purpose of making this work is to 1. Create a written batik motif design with the source idea of Pithecanthropus Erectus with a blend of primitive and modern styles 2. Create a haute couture fashion design with a source of batik ideas from pithecanthropus erectus combining primitive and modern styles 3. Apply the Pithecanthropus written batik motif Erectus into Haute Couture fashion design. The method in creating this work uses the principle of 3 stages, namely Exploration, Design and Realization. The final work produced is in the form of 5 Haute couture clothing with abstract coloring techniques on batik motifs. The finished batik cloth is combined with brocade and toyyobo fabrics which are applied to haute couture clothing. The motif title for this work is